Recent updates on GPCR biased agonism. (October 2016) - Pupo, André S.; Duarte, Diego A.; Lima, Vanessa; Teixeira, Larissa B.; Parreiras-e-Silva, Lucas T.; Costa-Neto, Claudio M.
Graphical abstract: Abstract: G protein-coupled receptors (GPCRs) are the most important targets for drug discovery and not surprisingly ∼40% of all drugs currently in the market act on these receptors. Currently, one of the most active areas in GPCRs signaling is biased agonism, a phenomenon that occurs when a given ligand is able to preferentially activate one (or some) of the possible signaling pathways. In this review, we highlight the most recent findings about biased agonism, including an extension of this concept to intracellular signaling, allosterism, strategies for assessment and interpretation, and perspectives of therapeutic applications for biased agonists.